Participación de la familia en la formación integral de los niños de la Escuela de Educación Básica "Aquiles Perez Tamayo", parroquia Chugchilan del cantón Sigchos. - Curay Chiluisa, Ana del Rocio (2018)
This research project is an important issue because of the parents' participation in their children's education is transcendental; when parents participate in the teaching of children, they obtain better results, they have positive attitudes towards school, and they grow up to be successful in life. The objective was to determine the participation of the family in the comprehensive education of children, through diagnostic and bibliographic research to raise awareness among parents about the importance of the educational process of their children at the Aquiles Perez Tamayo School of Sigchos Canton, Cotopaxi Province. To carry out this research, the inductive, deductive, analytical, statistical method were used which were used according to the need of the theme. The investigative work is based on theoretical bases such as the types of family, family structure, family participation, advantages, the educational community, elements of the educational community, and integral formation. The study has a qualitative approach, descriptive research type to the description and analysis of the problem, field, and bibliographic-documentary; the interview were used to obtain data and information which allowed to know the personal criteria of the teachers, and the survey through the application of a questionnaire, after that the data collected was tabulated and interpreted, through the descriptive statistics by using the Excel program, to draw the conclusions and recommendations; among the results obtained from parents, it was evident that they do not have a level of education to help their children in school tasks.